The role of the Consultant Radiographer in facilitating rapid access to palliative radiotherapy. Issue 4 (November 2021) - Fisher, S.
Abstract: Introduction: The fast track pathway for palliative radiotherapy was created to facilitate rapid access to radiotherapy for symptom relief and improved quality of life. The fast track pathway has a target of 5 days from the decision to treat to starting treatment. Methods: This study is a quantitative analysis of all patients referred and treated with palliative radiotherapy between the 1st September 2018 and 30th September 2019. The number of working days overall from referral to treatment and at each stage of the radiotherapy pathway was recorded and evaluated. The electronic referral system was amended to include the treatment priority option of 'fast track' for all patients with the selected treatment intent of 'palliative'. The data was acquired using the electronic referral system reporting tool. Results: Results demonstrate a reduction in average pathway timing from 14 days to 3 days for volume planned patients, and 13 days to 2 days for virtual simulation patients referred into the fast track pathway. The routine priority palliative pathway also demonstrated a decrease in time from decision to treat to treatment, despite this not being an initial objective. Conclusion: Reducing pathway time from referral to treatment is achievable through the introduction of a fast track treatment priority pathway. Rapid access to treatment was facilitated through the electronic referral system fast track option, the creation of a separate fast track care path in Aria, the use of fast track alerts in Aria, and reserved planning scan and treatment appointments. Implications for practice: Rapid access to palliative radiotherapy facilitates alleviation of symptoms and improved quality of life. To improve the efficiency of the palliative radiotherapy service, a streamlined pathway and the commitment of the radiotherapy team is required.